2016
DOI: 10.1371/journal.ppat.1005570
|View full text |Cite
|
Sign up to set email alerts
|

ToxR Antagonizes H-NS Regulation of Horizontally Acquired Genes to Drive Host Colonization

Abstract: The virulence regulator ToxR initiates and coordinates gene expression needed by Vibrio cholerae to colonize the small intestine and cause disease. Despite its prominence in V. cholerae virulence, our understanding of the direct ToxR regulon is limited to four genes: toxT, ompT, ompU and ctxA. Here, we determine ToxR’s genome-wide DNA-binding profile and demonstrate that ToxR is a global regulator of both progenitor genome-encoded genes and horizontally acquired islands that encode V. cholerae’s major virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 114 publications
(175 reference statements)
6
58
0
Order By: Relevance
“…Since many of these phenotypes have also been associated with ToxR, these results suggest that ToxR regulates many of its gene targets indirectly. This conclusion is supported by the aforementioned ChIP-seq studies indicating that ToxR directly regulated just 39 genes (49). The gene encoding LeuO was among the 39 genes identified in the ChIP-seq data set, confirming our previous reports that ToxR directly regulated leuO transcription (10,11).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Since many of these phenotypes have also been associated with ToxR, these results suggest that ToxR regulates many of its gene targets indirectly. This conclusion is supported by the aforementioned ChIP-seq studies indicating that ToxR directly regulated just 39 genes (49). The gene encoding LeuO was among the 39 genes identified in the ChIP-seq data set, confirming our previous reports that ToxR directly regulated leuO transcription (10,11).…”
Section: Discussionsupporting
confidence: 89%
“…This conclusion is supported by microarray studies which implicated ToxR in the regulation of Ͼ150 genes in V. cholerae, including genes involved in cellular transport, energy metabolism, motility, iron uptake, and outer membrane proteins (30). This conclusion is further supported by a recently published ToxR chromatin immunoprecipitation sequencing (ChIP-seq) study showing that ToxR can function as an H-NS antagonist (49). We previously showed that ToxR directly activated leuO expression in response to environmental cues by a process that was dependent upon the presence of the periplasmic domain of ToxR (10,11).…”
Section: Discussionmentioning
confidence: 68%
“…A similar pattern was observed in independent ChiP-Seq analysis using a different El Tor biotype V. cholerae strain (Fig. 1) [31]. H-NS bound to fewer sites along V. cholerae chromosomes, but occupied longer stretches of DNA compared to E. coli .…”
Section: H-ns Global Regulation and Chromatin Binding In V Choleraesupporting
confidence: 81%
“…Another example is provided by the bitopic regulator ToxR. The cytoplasmic domain of the transmembrane protein ToxR directly activates the transcription of toxT , ompU and ompT (encoding outer membrane proteins) and the vpsL-Q operon while remaining anchored to the inner membrane [31,36]. The bridging activity of H-NS could facilitate chromosome-inner membrane interactions at several sites, allowing ToxR molecules to simultaneously engage multiple target promoters.…”
Section: H-ns Global Regulation and Chromatin Binding In V Choleraementioning
confidence: 99%
“…Notable mutations across the sequential strains first include a G107S mutation in the histone-like protein H-NS, which is in the DNA binding domain of this repressor that controls transcription of genes that encode hemolysin, MARTX, and CT (39). A recent study showed that deletion of hns uncouples virulence gene expression from its normal control by ToxR, which could account in part for the increased toxin production (40).…”
Section: Overproduction Of Secreted Toxins By An Aet Isolate From Haitimentioning
confidence: 99%